If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 8) = 48 Reorder the terms: 6(8 + x) = 48 (8 * 6 + x * 6) = 48 (48 + 6x) = 48 Add '-48' to each side of the equation. 48 + -48 + 6x = 48 + -48 Combine like terms: 48 + -48 = 0 0 + 6x = 48 + -48 6x = 48 + -48 Combine like terms: 48 + -48 = 0 6x = 0 Solving 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = 0 Simplifying x = 0
| 7/8x=-2/3 | | 4x-25=5x | | 4d+6-6d=120 | | a+54=69 | | 1/2y=6x-5/9 | | -2y^2-7y+39=0 | | 25+6x-7=36 | | Y+4y+10=5(y+2) | | -15+6x=-24+6x+9 | | 12x=y-5 | | Cd-4=5cford | | 4(15+12)+5(8)= | | 8c+5-5c+7=36 | | 5(2-x)=2(4+3x) | | 12-1x=3x | | 3x+-4+2x=0 | | Ln(x^3)-3=0 | | b/16=5 | | 4(a+12)+5(8)= | | 3/4t-5.8 | | 12x-2=3x+14 | | -2n^2+15n-13=0 | | 154=x^2+15x | | -4y-12x=4 | | 2n^2+15n-13=0 | | 0.4*x=75000 | | a-32=29 | | 3x+14=-82 | | 4x^2-50x+486=0 | | t=16t^2+3136 | | X/2-8=6 | | 7.9+d=12 |